Host–virus interactions: from the perspectives of epigenetics. (21st February 2014) - Li, Shanshan; Kong, Lingbao; Yu, Xilan; Zheng, Yi
SUMMARY Chromatin structure and histone modifications play key roles in gene regulation. Some virus genomes are organized into chromatin‐like structure, which undergoes different histone modifications facilitating complex functions in virus life cycles including replication. Here, we present a comprehensive summary of recent research in this field regarding the interaction between viruses and host epigenetic factors with emphasis on how chromatin modifications affect viral gene expression and virus infection. We also describe the strategies employed by viruses to manipulate the host epigenetic program to facilitate virus replication as well as the underlying mechanisms. Together, knowledge from this field not only generates novel insights into virus life cycles but may also have important therapeutic implications. Copyright © 2014 John Wiley & Sons, Ltd.